Interdisciplinary Relations Between Police Science and Applied Linguistics — Forensic Linguistics - Tolnainé Kabók, Zsuzsanna (Magyar Rendészet, 2016)
There are interdisciplinary contacts between Law Enforcement and Applied Linguistics as well. Forensic linguistics as an independent discipline helps law enforcement activities. It is quite certain that the role of forensic linguistics in law enforcement will grow in Hungary, too, in the future. That is why it seems to be indispensable to introduce an innovative post-gradual training in forensic linguists. The most suitable institution for this purpose could be the National University of Public Service.